Motivation of learning: An assessment of the practicality and effectiveness of gamification within a tertiary education system in Malaysia. - Ong, Derek Lai Teik *; Chan, Yuen Yeng *; Cho, Wai Hong *; Koh, Tse Young * (2013)
In light of the many criticisms about the Malaysian education system unable to stimulate intrinsic academic motivation among students, this research paper aims to address this issue by assessing the practicality and effectiveness of implementing gamification within education as a viable solution. To do so, the variable factors that determine the effectiveness of gamification need to be identified. Through extensive journal research, the two main factors were identified as past gaming experience (PGE) influenced by intrinsic gaming motivation and personality/learning styles. Through a total of 186 surveys collected, it is found that university students’ perceived effectiveness of gamification is largely independent of past gaming experience and personality/learning styles, except for reducing academic amotivation and stimulating intrinsic motivation. Despite unable to find a suitable model to explain the factors of an effective gamified education, this paper has met its objectives by confirming the fact that gamification does in fact help to tackle the academic motivational problem Malaysia’s education system is currently facing. Furthermore, backed with a mild positive general response from students, it shows that gamification, being independent of past gaming experience and personality/learning style is practical and effective among all students when applied in Malaysia.